2002
DOI: 10.1002/art.10531
|View full text |Cite
|
Sign up to set email alerts
|

Relative messenger RNA expression profiling of collagenases and aggrecanases in human articular chondrocytes in vivo and in vitro

Abstract: Objective. Osteoarthritic (OA) cartilage destruction depends on collagen-and aggrecan-degrading proteases such as collagenases (MMP-1 and MMP-13), stromelysin (MMP-3), MMP-14, as well as the so-called aggrecanases (ADAM-TS4 and ADAM-TS5). In this study, we tried to clarify whether these proteases are expressed in vivo in human normal and OA cartilage (and whether they are up-regulated or down-regulated during the disease process) and in interleukin-1␤ (IL-1␤)-stimulated chondrocytes in vitro.Methods. Quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

40
326
2
7

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 370 publications
(375 citation statements)
references
References 84 publications
40
326
2
7
Order By: Relevance
“…Studies of human articular chondrocytes have shown that in vivo levels of MMP13 are significantly lower than in cells cultured in vitro, but the responses to IL-1␤ are similar (49). Our analysis of MMP13 mRNA expression levels in articular chondrocytes showed that basal levels were lowest in the youngest animals and increased ϳ3-fold in adult and mature animals.…”
Section: Discussionmentioning
confidence: 64%
“…Studies of human articular chondrocytes have shown that in vivo levels of MMP13 are significantly lower than in cells cultured in vitro, but the responses to IL-1␤ are similar (49). Our analysis of MMP13 mRNA expression levels in articular chondrocytes showed that basal levels were lowest in the youngest animals and increased ϳ3-fold in adult and mature animals.…”
Section: Discussionmentioning
confidence: 64%
“…35 In chondrocytes, ADAMTS4 was induced by Il-1b. 36 ADAMTS4 and 5 inductions in glioblastoma cells is partly similar, but not completely identical as in mesenchymal cells. It is well known that TGF-b is a major cytokine produced by high grade gliomas and is, therefore, an example for the regulation of these proteases in the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 83%
“…Proinflammatory stimuli may upregulate transcription of aggrecanase genes (Bau, et al, 2002;Koshy, et al, 2002), and there is mounting evidence for substantial post-translational processing of the enzymes that alter aggrecanase activity and specificity (Pratta, et al, 2003a). In human chondrosarcoma cells and bovine cartilage explants, MMP-17 (MT4-MMP) appears to be responsible for C-terminal truncation of ADAMTS-4, a process which converts the enzyme from one which can cleave only the sGAG-rich region to one which can also cleave the interglobular domain (IGD) (Gao, et al, 2004;Patwari, et al, 2005).…”
Section: Introductionmentioning
confidence: 99%